DIGITAL CONSTITUTIONALISM ERA IN THE DEVELOPMENT OF BANKING LAW IN INDONESIA - Putri, Mery Christian; Kurniawan, Nalom (Journal of Central Banking Law and Institutions, 2022)
Digitalisation has changed, bringing the world in an almost borderless direction, and impacting various fields. Banking law in particular has been disrupted by the rapid development of digitalisation, as well as shifting paradigms of thinking across the banking world. As a result of the digital economy era, conventional banking services have been forced to adapt to the development of the concept of digital constitutionalism. The digital economy era must provide better banking services to guarantee the protection of citizens’ constitutional rights, especially related to the use of technology in banking services. This concept of the digital economy must be able to improve the quality of banking services in terms of ease and speed of access, efficiency, effectiveness, and optimal management of risk. Thus, it is expected that the development of the era of digital constitutionalism in banking law in Indonesia can provide a more optimal guarantee of protection of future constitutional rights protection for its citizens. This study describes the transitional process of the digital constitutionalism era in the development of banking law in Indonesia as a factual condition by using normative juridical research methods and library approaches, as well as comparative approaches. The study finds that the development of the digital constitutionalism era in banking law in Indonesia has progressed rapidly. This progress has benefitted users of banking services, but it also has led to a residual deviant behaviour due to the ease of access to technology.